Measuring the environmental impacts of changing trade patterns on the poor - Kaliappa Kalirajan; Venkatachalam Anbumozhi; Kanhaiya Singh (Asian Development Bank Institute (ADBI), 2010)
It is an empirical fact that it is very difficult to balance economic growth, poverty reduction, and environment protection, particularly for developing and transitional economies. While the economic environment of a country is influenced by conditions within the country, it is also influenced by external shocks such as the recent global financial crisis depending on how integrated the country is with the rest of the world. Thus, it poses a continuing challenge for policy makers in developing and transitional countries to readjust the economic environment in a way that leads to better and more effective targeting of the chronic issue of poverty reduction without causing damage to the natural environment. It is in this context that this paper attempts to measure the environmental impact of changing trade patterns on the poor. The recent financial crisis has discouraged United States (US) private consumption, which in turn has significantly reduced exports from Asia. However, Asia's private consumption is at a very low level even when compared with the current reduced US private consumption. Therefore, it is possible for Asian countries to focus more on improving regional trade and domestic consumption to compensate for the revenue losses that resulted from the reduction in global demand. This paper argues that energy-efficient production methods and service-led growth, particularly trade in environmental goods and services, provide good opportunities for Asian countries to enjoy inclusive growth without damaging the natural environment.
Keywords: E20; Q43; Q56; 330; Exportinduziertes Wachstum; Umweltschutz; Außenhandelsstruktur; Armut; Asien